2003
DOI: 10.1038/sj.onc.1206574
|View full text |Cite
|
Sign up to set email alerts
|

MBD1, MBD2 and CGBP genes at chromosome 18q21 are infrequently mutated in human colon and lung cancers

Abstract: The genes MBD1 and MBD2 encode methyl-CpG binding proteins that suppress transcription from methylated promoters. In contrast, CGBP encodes a protein that binds promoters containing unmethylated CpG and stimulates transcription. All three are located on human chromosome 18q21, a region of frequent loss of heterozygosity in several cancers. These genes therefore represent candidate tumour suppressor genes, whose loss of function could affect the normal regulation of gene expression, whether by lack of complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
(48 reference statements)
0
19
0
Order By: Relevance
“…Previous study reported that the upregulation of MBD1 enhanced the epithelial mesenchymal transition and invasion of pancreatic cancer cells [14], which suggested that MBD1 contributed to the tumor growth in pancreatic cancer. Another study reported that deletion of 18q21 chromosome where MBD1 was located occurred frequently in CRC [15, 16], which suggested that genes in 18q21 chromosome zone might inhibit tumor growth in CRC. The deletion of 18q21 chromosome could result in the abnormal activation of cancer genes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that the upregulation of MBD1 enhanced the epithelial mesenchymal transition and invasion of pancreatic cancer cells [14], which suggested that MBD1 contributed to the tumor growth in pancreatic cancer. Another study reported that deletion of 18q21 chromosome where MBD1 was located occurred frequently in CRC [15, 16], which suggested that genes in 18q21 chromosome zone might inhibit tumor growth in CRC. The deletion of 18q21 chromosome could result in the abnormal activation of cancer genes.…”
Section: Discussionmentioning
confidence: 99%
“…39 Nevertheless, frequent MBD1 mutations have not yet been detected in human colon or lung tumors. 40 Furthermore, constitutive knockout of MBD1 does not seem to generate any overt tumor phenotype in mice, although increased genomic instability has been reported in neural-stem cells. 41 Hence, on the basis of the current data in the literature, it is not clear whether MBD1 has a substantial role in modifying tumorigenesis.…”
Section: Methyl-binding Domain Proteinmentioning
confidence: 99%
“…Expression analysis of MBD proteins in tumours has revealed increased overall levels associated with enhanced proliferation (Esteller, 2005a). Mutations in MBDs do occur in sporadic tumours, albeit rarely (Bader et al, 2003). MBD4 is an exception and is frequently targeted by inactivating frameshift mutations in microsatellite-unstable tumours (Riccio et al, 1999).…”
Section: Estellermentioning
confidence: 99%